"(NmAZEPA (B"(Np(B. (Ni(B.(N~AJKOWSKOGOs (NMONOGRAFIQs ((NmOSKWAs (NmUZYKAs, 1989)
(NdOSTOJNOE MESTA W \TOM RQDU ZANIMAET OPERA p (B.(Ni(B.(N~AJKOWSKOGO (B"(NmAZEPA (B".s
Keywords: (NoPERNYJ LIBRETTOs